Employment effects of innovations over the business cycle: firm-level evidence from European countries - Dachs, Bernhard; Hud, Martin; Koehler, Christian; Peters, Bettina (Mannheim, 2016)
"A growing literature investigates how firms’ innovation input reacts to changes in the business cycle. However, so far there is no evidence whether there is cyclicality in the effects of innovation on firm performance as well. In this paper, we investigate the employment effects of innovations over the business cycle. Our analysis employs a large data set of manufacturing firms from 26 European countries over the period from 1998 to 2010. Using the structural model of Harrison et al. (2014), our empirical analysis reveals four important findings: First, the net effect of product innovation on employment growth is pro-cyclical. It turns out to be positive in all business cycle phases except for the recession. Second, product innovators are more resilient to recessions than non-product innovators. Even during recessions they are able to substitute demand losses from old products by demand gains of new products to a substantial degree. As a result their net employment losses are significantly lower in recessions than those of non-product innovators. Third, we only find resilience for SMEs but not for large firms. Fourth, process and organizational innovations displace labor primarily during upturn and downturn periods."